Respuesta :

the first step to solving this is to use a² - b² = (a - b)(a + b) to factor the expression
2√3 × 2x = 8√3
now calculate the product 
4√3x = 8√3
finally,, divide both sides of the equation by 4√3
x = 2.
this means that the correct answer to your question is x = 2.
let me know if you have any further questions
:)
[tex](x + \sqrt{3} ) {}^{2} - (x - \sqrt{3} ) { }^{2} = 8 \sqrt{3} [/tex]

Using (a² - b²) = (a + b)(a - b):
[tex](x + \sqrt{3} + x - \sqrt{3} )(x + \sqrt{3} - x + \sqrt{3} ) = 8 \sqrt{3}[/tex]

Combine like terms in the brackets:
[tex](2x)(2\sqrt{3}) = 8 \sqrt{3}[/tex]

Simplify LHS:
[tex]4x\sqrt{3} = 8 \sqrt{3}[/tex]

Divide by √3 on both sides:
[tex]4x = 8 [/tex]

Divide by 4 on both sides:
[tex]x = 2[/tex]